Etika Deontologis dan Kebajikan: Fondasi Meningkatkan Akuntabilitas Birokrasi : (Studi di Dinas Sosial Kabupaten Bima) - Nurfarhati Nurfarhati; Mukhlis Ishaka; Haeril Haeril (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to explore and analyze how the integration of deontological ethics and virtue ethics can serve as a foundation for enhancing accountability and transparency in the Social Services Department of Bima Regency, focusing on the understanding and application of ethical principles by civil servants and their impact on governance. Employing a qualitative descriptive method, this research involved in-depth interviews, participatory observation, and documentation studies to collect data from various informants directly involved in the implementation and supervision of bureaucratic ethics. Data analysis was conducted through an iterative model, including data reduction, data display, and conclusion drawing to gain a deep understanding of the dynamics of deontological and virtue ethics in the bureaucratic environment of Bima Regency. The findings indicate that although the integration of deontological and virtue ethics holds great potential in enhancing transparency and accountability, real challenges are faced, including the misalignment between ethical principles and bureaucratic operational realities, resistance to change, and weaknesses in the oversight system. These findings highlight the importance of comprehensive ethical education and training, the development of effective accountability mechanisms, and increased community participation as key strategies to overcome these challenges and strengthen the ethical foundation in the governance of Bima Regency.